Population Dynamics of Narrow-Bareed Mackerel (Scomberomorus commersonii) and Wolf Herring (Chirocentrus dorab) in Malacca Strait Waters - Mardiyah, Wilda; Fauzi, Muhammad; Efizon, Deni (Jurnal Perikanan dan Kelautan, 2022)
Narrow barred Spanish mackerel and wolf herring is an important commodity that has commercialized intensively to fulfill the needs of the market, both domestic and export. Research has been conducted from June-August 2020 in Malacca Strait Waters. The purpose of this study is to analyze the dynamics of population parameters such as growth rate, mortality rate, exploitation rates, and recruitment patterns of narrow barred mackerel (Scomberomorus commerson) and wolf herring (Chirocentrus dorab). The Sample size of spanish mackerel was taken at randomly from the purse seiner and gillnet catches. Data of size obtained were used for the analysis of population dynamics parameters. Some population dynamics parameters were estimated using the program FISAT II. Von Bertalanffy growth parameters of spanish mackerel were derived L and growth rate (K),for males 772.8 mm and 0.5/year and for females 979.65 mm and 1,7/year and wolf herring was derived L and growth rate (K), for males 871.5 mm and 0.59/year, and for females 1048.95 mm and 0.65/year, respectively. Total mortality (Z) of spanish mackerel males and females was 0.61/year and 4.07/year and the wolf herring males and females was 0.36/year and 1,3/year. Fishing mortality rate of spanish mackerel (F) for males and females was 0,13/year and 3.07/year high than natural mortality rate (M) 0.48/year and 1/year and wolf herring fishing mortality rate for males and females was 0.16/year and 0.78/year lower than natural mortality rate (M) 0.52/year. Exploitation rate (E) of spanish mackerel for males and females was 0.21/year and 0.75/year and wolf herring for males and females was 0.44/ year and 0,6/year, that almost full exploitation when compared with optimum of 0.40. The recruitment pattern of Spanish mackerel for males was (14.59%) in June and for females was (26.84%) in August and wolf herring for males was (16.02) in June, and for females was (28.63%) in July.